(untitled) (The Review of Diabetic Studies, 2024)
Background: Shared decision-making (SDM) has become a fundamental component of patient centered care, especially for individuals with end-stage renal disease (ESRD) receiving hemodialysis. Nurses are at the core of this process, as their professionalism, empathy, and clinical decision-making ability directly shape patients’ involvement in treatment decisions. Despite growing global evidence, little is known about how these factors influence SDM awareness among hemodialysis nurses in Saudi Arabia. Aim: This study aimed to examine the effects of nursing professionalism, empathy, and clinical decision-making ability on SDM awareness among hemodialysis nurses and to identify their combined predictive power. Methods: A cross-sectional quantitative design was employed among 182 hemodialysis nurses from tertiary hospitals in Saudi Arabia. Data were collected using validated instruments, including the Nursing Professionalism Scale, Jefferson Scale of Empathy (HP version), Clinical Decision-Making in Nursing Scale, and Shared Decision-Making Questionnaire. Descriptive statistics, Pearson’s correlations, multiple regression, and mediation analysis (PROCESS macro) were performed, with significance set at p < 0.05. Results: Nurses demonstrated moderately high levels of professionalism (M = 3.82, SD = 0.49), empathy (M = 104.7, SD = 11.9), decision-making ability (M = 3.64, SD = 0.42), and SDM awareness (M = 4.01, SD = 0.58). Correlation analysis revealed significant positive associations among all study variables. Regression analysis showed that professionalism, empathy, and decision-making collectively explained 45% of the variance in SDM awareness (Adjusted R² = 0.45, p < 0.001), with empathy emerging as the strongest predictor. Mediation analysis confirmed that empathy partially mediated the relationship between professionalism and SDM awareness. Conclusion: Professionalism, empathy, and decision-making ability significantly influence SDM awareness among hemodialysis nurses, with empathy playing a central role. These findings highlight the importance of integrating empathy training, professional values, and decision-making skills into nursing education and practice. Strengthening these competencies will not only improve patient-centered care but also contribute to achieving Saudi Vision 2030 objectives for healthcare transformation and patient empowerment.